Are we heroes or couriers? A phenomenological study on reappropriation of professional subjectivity and agency among health professionals during COVID-19 contact tracing in Türkiye - Polat, Ayşe; Demircioğlu, Zübeyde; Küçükali, Hüseyin (My University, 2024)
During the COVID-19 pandemic, Türkiye implemented a distinctive contact tracing approach involving in-person home visits by medical professionals to individuals who tested positive for the virus. This study examines the experiences of health professionals involved in contact tracing, exploring how they reappropriated their professional subjectivity and agency during their deployment in this role. It is an interpretive phenomenological qualitative study. We conducted 21 semi-structured in-depth interviews, subsequently carried out two separate focus group interviews with an additional 31 participants from various districts in Istanbul. Participants were selected from different medical professions (i.e. doctors, nurses, midwives), career stages, gender and age groups, and hierarchical levels (i.e. officers and directors). Data analysis was conducted collaboratively by the research team from sociology and public health disciplines. Our main finding is that for the majority of health professionals, contact tracing was a novel experience with challenges and ambivalances. Yet, regardless of their perceptions (positive, negative, or mixed), the experience promoted a reaffirmation of professional identity and reappropriation of professional subjectivity and agency, which discloses that professional subjectivity is not firm but dynamic, carrying stability as well as flexibility and adjustment. Four main themes are identified in their reappropriation of professional subjectivity and agency: uncovering professional fulfillment, feeling restrained in professional dissatisfaction, assessing the job, and engaging in professional and bureaucratic negotiations.The profound exploration into the dynamics of contact tracing amidst the pandemic illuminates a multidimensional narrative that transcends the conventional discourse on physical and psychological stress experienced by medical professionals. Contact tracing experience had a transformative impact on meaning and purpose of professional identity. Our findings highlight a need for a balanced approach between centralized decision-making, mobilization of professionals, quantitative evaluation, and professional autonomy and discretion, qualitative assessments, and meaningful engagement.
Keywords: Agency; Contact Tracing; Health Professionals; Health Workers; Pandemic; Subjectivity